Forensic identity SNPs: Characterisation of flanking region variation using massively parallel sequencing. (May 2023) - Davenport, Lucinda; Devesse, Laurence; Syndercombe Court, Denise; Ballard, David
Abstract: Single nucleotide polymorphisms (SNPs) can be analysed for identity or kinship applications in forensic genetics to either provide an adjunct to traditional STR typing or as a stand-alone approach. The advent of massively parallel sequencing technology (MPS) has provided a useful opportunity to more easily deploy SNP typing in a forensic context, given the ability to simultaneously amplify a large number of markers. Furthermore, MPS also provides valuable sequence data for the targeted regions, which enables the detection of any additional variation seen in the flanking regions of amplicons. In this study we genotyped 977 samples across five UK-relevant population groups (White British, East Asian, South Asian, North-East African and West African) for 94 identity-informative SNP markers using the ForenSeq DNA Signature Prep Kit. Examination of flanking region variation allowed for the identification of 158 additional alleles across all populations studied. Here we present allele frequencies for all 94 identity-informative SNPs, both including and excluding the flanking region sequence of these markers. We also present information on the configuration of these SNPs in the ForenSeq DNA Signature Prep Kit, including performance metrics for the markers and investigation of bioinformatic and chemistry-based discordances. Overall, the inclusion of flanking region variation in the analysing workflow for these markers reduced the average combined match probability 2175 times across all populations, with a maximum reduction of 675, 000-fold in the West African population. The gain due to flanking region-based discrimination increased the heterozygosity of some loci above that of some of the least useful forensic STR loci; thus demonstrating the benefit of enhanced analysis of currently targeted SNP markers for forensic applications. Highlights: Performance evaluation of the 94 iiSNP loci targeted by the ForenSeq DNA Signature Prep Kit. Characterisation of flanking region variation observed and corresponding allele frequency data for five UK population groups. Flanking region variation increases heterozygosity in 70% of targeted loci, showing the power of analysing SNP loci with MPS.